The Shoulder - Huri, Gazi; Paschos, Nikolaos K. (Springer International Publishing : Imprint: Springer, 2017)
This book provides a broad overview of operative and non-operative treatments of various conditions affecting the shoulder. It is presented in an easy to use format with each chapter including multiple choice questions to assist the reader in preparing for boards to improve shoulder knowledge and increase success in exams. The Shoulder clearly describes the basic science, anatomy, biomechanical features and principals of physical examination while utilising an algorithmic approach to shoulder disorders. The contributors are an international team of shoulder experts who understand what is important to know at every level. The result is a book of value to those new to shoulder challenges and also experienced surgeons who wish to have a quick and handy guide to current concepts and knowledge of shoulder conditions and treatment.
Keywords: Medicine.; Orthopedics.; elektronické knihy; electronic books